Rebranding Perception and Intention to Use Mental Health Services: The Mediating Role of Destigmatization - Era Catur Prasetya; Timotius FCW Sutrisno; Anak Agung Ayu Puty Andrina (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2025)
Mental health services in Indonesia continue to face challenges due to persistent stigma, which often prevents individuals from seeking professional help. In response, the Mindscape Clinic at Muhammadiyah Hospital initiated a comprehensive rebranding program aimed at transforming public perception and reducing stigma. This study employed a quantitative cross-sectional design with a purposive sample of 120 respondents who had used the clinic’s services within the last six months. Data were collected using three validated instruments measuring rebranding perception, destigmatization, and service intention, and were analyzed using descriptive statistics, Pearson correlations, and mediation analysis with PROCESS macro. Results revealed that respondents perceived the clinic’s rebranding positively (M = 3.92, SD = 0.68), with redesigning (M = 4.12) and repositioning (M = 4.05) rated highest, while renaming was rated lowest (M = 3.67). Correlation analysis confirmed strong positive relationships among the three variables, while mediation analysis showed that destigmatization partially mediated the effect of rebranding perception on service intention, explaining 51% of the total effect. These findings highlight that rebranding functions not only as a marketing initiative but also as a psychosocial intervention that reduces stigma and enhances public willingness to utilize mental health services.